2017
DOI: 10.1002/adsc.201700840
|View full text |Cite
|
Sign up to set email alerts
|

Transition Metal‐Catalysed Intramolecular Carbenoid C−H Insertion for Pyrrolidine Formation by Decomposition of α‐Diazoesters

Abstract: The use of Pd-, Rh(II)-and Ru(II)-based catalysts has been explored in the transition metalcatalysed intramolecular carbenoid CÀH insertion of a-diazoesters leading to pyrrolidines. Although the outcome of the reaction was highly substrate-dependent, in general, it was possible to control the chemoselectivity of the process towards pyrrolidines by adequate catalyst selection. The Pd(0)-catalysts were as efficient as [Rh(Ph 3 CCO 2 ) 2 ] 2 in promoting the C(sp 3 )ÀH insertion of ortho-substituted anilines. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 63 publications
1
6
0
Order By: Relevance
“…Interestingly, similar to the reaction of 1 j , tetrahydroquinoline formation was enhanced by the use of the Pd 0 catalyst, which afforded a 1:1 mixture of 2 k and 3 k . The high tendency of ortho ‐substituted aniline 1 k to undergo sp 3 ‐C−H functionalization, which is in line with our previously reported results, can be mainly ascribed to steric factors.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Interestingly, similar to the reaction of 1 j , tetrahydroquinoline formation was enhanced by the use of the Pd 0 catalyst, which afforded a 1:1 mixture of 2 k and 3 k . The high tendency of ortho ‐substituted aniline 1 k to undergo sp 3 ‐C−H functionalization, which is in line with our previously reported results, can be mainly ascribed to steric factors.…”
Section: Resultssupporting
confidence: 92%
“…In our studies on the TM‐catalyzed reactions of γ‐amino‐α‐diazoesters, we found that the use of either [Pd 2 (dba) 3 ] (dba=dibenzylideneacetone) or [{Pd(IMes)(NQ)} 2 ] (IMes=1,3‐dimesitylimidazol‐2‐ylidene, NQ=1,4‐naphthoquinone) as catalysts to promote the decomposition of N ‐isopropyl α‐diazoester 1 a resulted in chemoselective functionalization at the arylic sp 2 ‐C−H bond to give tetrahydroquinoline 2 a (Table , entries 1 and 2). With these data in hand, we began by testing the use of Grubbs catalysts Ru‐1 , Ru‐2 , and Ru‐3 (Figure ) to promote the annulation reaction from 1 a .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Continuing our search for methodologies to enhance the synthetic potential of organopalladium chemistry, we have also investigated the versatility of palladium as a catalyst for the carbene C–H insertion. In this context, we reported that palladium catalysts are able to promote Csp 3 –H insertion of carbenes derived from α-diazoesters to form pyrrolidines through intramolecular Csp 3 –Csp 3 bond formation [53,54].…”
Section: Introductionmentioning
confidence: 99%
“…7 Meanwhile, Buchner reaction of α-alkyl-αdiazoesters predominantly results in β-hydrogen migration to give α,β-unsaturated esters. 5,8 Despite extensive research on the intramolecular Buchner reaction, only one example demonstrated 5,7-fused ring formation with high chemoselectivity over β-hydride migration. 9,10 Moreover, its enantioselective variant has not been reported to our knowledge.…”
mentioning
confidence: 99%